Demokratisasi Desa dan Partisipasi Politik: Menurunnya Partisipasi dan Dukungan Warga dalam Pelaksanaan “Politik Lokal” di Bulungan-Pati - Ibnu Mujib (IKIP Budi Utomo Malang, 2017)
This study wants to keep track of public participation in responds to development of uncertaintly local democratic. This idea is based on an assumption of declining public participation in the previous elections of 2004. This study tries to observe how the development of democracy at the grassroots level can be inﬂuenced by extends political effect for imaging virtually designed and shaped by political pragmatism practices as conducted by the politicians in general. The fndings of this study explained that the democratization at the level of village/local is not understood as an urgent need, therefore the political participation of society is still in the category of “anut grubyuk” participation profess that is not based on the ideals and demands the real political rights of citizenship. The forms of participation are thus precisely met the drying times of democracy itself. It means that the future death of village democratization not only addressed because of the laziness of residents to political participation, but the attitude of the political elite is also partly responsible, especially in negotiating the political choices to rural communities in general.